Applying punctuated equilibrium theory to municipal and county operating and capital budgets. Issue 4 (1st March 2016) - Kovari, John
Abstract : Although punctuated equilibrium theory (PET) is widely hailed as the dominant theory regarding public policy and budgets, little research has extended PET to the local government arena or to capital expenditures. This article utilizes a panel dataset of public expenditures from Wisconsin counties, cities, villages, and towns from 1990-2009 to show that local operating and capital budgets fit the contemporary PET framework. However, the article also offers some discussion about methodological problems in assessing PET for local governments, and highlights the importance of differentiating between expenditure types (e.g. capital versus operating spending) as well as institutional differences between counties, cities, villages, and towns.